Additional Evidence for the Reliability and Validity of the Student Risk Screening Scale at the High School Level: A Replication and Extension. (June 2013) - Lane, Kathleen Lynne; Oakes, Wendy P.; Ennis, Robin Parks; Cox, Meredith Lucille; Schatschneider, Christopher; Lambert, Warren
This study reports findings from a validation study of the Student Risk Screening Scale for use with 9th- through 12th-grade students ( N = 1854) attending a rural fringe school. Results indicated high internal consistency, test-retest stability, and inter-rater reliability. Predictive validity was established across two academic years, with Spring Student Risk Screening Scale (SRSS) scores differentiating students with low-, moderate-, and high-risk status on office discipline referrals, grade point averages, and course failures during the following academic year. Teacher ratings evaluating students' performance later in the instructional day were more predictive than teacher ratings evaluating students' performance earlier in the instructional day. Educational implications, limitations, and future research directions are presented.